<em><u>Answer:</u></em>
<em><u>Answer:the answer is zero </u></em>
<em><u>Answer:the answer is zero Step-by-step explanation:</u></em>
<em><u>Answer:the answer is zero Step-by-step explanation:when we add -42 and -54 the answer we get is -96. -96and +96 cut each other and then the answer is zero </u></em>
<em><u>
</u></em>
Answer:
0,1,2
Step-by-step explanation:
(x+2) = 2((x+1)+(x)
x+2 = 2x+2+2x
x+2 = 4x+2
-x -x
2 = 3x + 2
-2 -2
0/3 = 3x/3
0 = x
Answer:
(x,y) -> (-x,y)
Step-by-step explanation:
The image is flipped over the x axis.
Answer:
i believe its d
Step-by-step explanation: